Model Social Cognitive Career Theory (SCCT) Dalam Menjelaskan Pilihan Karier Mahasiswa: Learning Experience, Self-Efficacy, dan Outcome Expectation - Yuniadi Mayowan (Jurnal Manajemen dan Pemasaran Digital, 2026)
This study aims to examine the cognitive mechanisms underlying career decision-making among university students by applying the Social Cognitive Career Theory (SCCT) framework. Specifically, it investigates the role of learning experiences in shaping self-efficacy and outcome expectations, which subsequently influence interest and career choice. Data were collected from 197 students at the Faculty of Administrative Sciences, Universitas Brawijaya, using a structured questionnaire. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that learning experiences significantly influence both self-efficacy and outcome expectations. Furthermore, self-efficacy and outcome expectations play a crucial role in shaping students’ career interests, which in turn significantly affect career choice. Among all variables, interest emerges as the most dominant predictor of career choice. These findings confirm the applicability of SCCT in the context of higher education and highlight the importance of experiential learning in enhancing students’ career readiness and decision-making processes.